Tracking key CAADP indicators and implementation processes [In the 2021 ATOR] - Tefera, Wondwosen; Collins, Julia; Makombe, Tsitsi (International Food Policy Research Institute, 2021)
In the 2003 Maputo Declaration on Agriculture and Food Security, African heads of state and government resolved to urgently implement the Comprehensive Africa Agriculture Development Programme (CAADP)—a continent wide framework for reducing poverty, food insecurity, and hunger and revitalizing agriculture through increased investments (AU 2003). Early on, the two main CAADP targets were allocating 10 percent of national budgets to the agricultural sector and achieving a 6 percent agricultural growth rate at the national level. In 2014, African leaders reasserted their commitment to CAADP and broadened the agenda by adopting the Malabo Declaration on Accelerated Agricultural Growth and Transformation for Shared Prosperity and Improved Livelihoods. Through seven broad commitments in the Malabo Declaration, the leaders resolved to uphold CAADP principles and values, increase investment in agriculture, end hunger and halve poverty by 2025, boost intra-African agricultural trade, enhance resilience to climate variability, and strengthen mutual accountability for actions and results by conducting a continental Biennial Review (BR) of progress made in achieving the commitments (AUC 2014).